Hubungan antara emotional eating pada mahasiswa Indonesia terhadap stres, faktor psikososial, dan status gizi: Sebuah tinjauan sistematis - Liza Fathiariani; Rina Hastuti Lubis (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2026)
Background: Emotional eating (EE) is an eating behavior influenced by emotional states and is increasingly reported among students, particularly in the context of academic pressure and changes in the socio-digital environment. Purpose: To synthesize evidence regarding the relationship between stress, psychosocial factors, emotional eating, and nutritional status among students in Indonesia. Method: This systematic review followed the PRISMA 2020 guidelines. Articles published between 2021 and 2026 were identified through systematic searches across multiple databases and selected based on established inclusion criteria. A total of 35 quantitative studies involving 5,181 participants were included in the narrative synthesis. Methodological quality was assessed using the Joanna Briggs Institute (JBI) instruments. Results: Of the 18 studies examining the relationship between stress and emotional eating, 16 (88.9%) reported a significant positive association, with correlation strengths ranging from weak to moderate (r = 0.14–0.45). Other psychosocial factors associated with emotional eating included emotion regulation, neuroticism, social media engagement, mindfulness, and exposure to “mukbang” content. Findings regarding the relationship between emotional eating and nutritional status were more varied; five of the nine studies reported a significant association with overweight or obesity, while four found no significant link. Additionally, emotional eating was consistently associated with unhealthy dietary patterns and increased consumption of energy-dense foods. Conclusion: Emotional eating is a common phenomenon among Indonesian students and is consistently associated with higher stress levels. Beyond stress, various psychological and social factors contribute to the occurrence of emotional eating. Although emotional eating tends to be linked to unhealthy dietary patterns, its association with overweight or obesity remains inconsistent. Keywords: Academic Stress; Emotional Eating; Nutritional Status; Students.